Một số ý kiến góp ý Chiến lược giáo dục giai đoạn 2021 - 2030, tầm nhìn đến năm 2045 - Chu Hồng Thanh (2022)
|Một số ý kiến góp ý Chiến lược giáo dục giai đoạn 2021 - 2030; Tầm Chiến lược giáo dục giai đoạn tầm nhìn đến năm 2045.